2021
DOI: 10.3390/ijerph18020633
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Health Literacy and Depressive Symptoms among Medical Students: An Analysis of Mediating Effects

Abstract: Depressive symptoms are prevalent in university students and may impair their social, educational, and economic transition into adulthood. Identifying the factors that determine depressive symptoms is crucial for the design of effective policy interventions. This study aims to examine the associations between health literacy and depressive symptoms among medical students, and to evaluate the effect of different types of social support as a potential mediator. A cross-sectional survey of medical students was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
18
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 42 publications
7
18
0
5
Order By: Relevance
“…This score represents about 68% of the maximum HL score (37 points) using this scale. Other studies (49)(50)(51) that used the same instrument showed similar HL scores to those of our study. Chinese adolescents (49) , mean age of 13.4 years, had a mean HL score of 26.3, a little higher than the score obtained in our study.…”
Section: Discussionsupporting
confidence: 87%
“…This score represents about 68% of the maximum HL score (37 points) using this scale. Other studies (49)(50)(51) that used the same instrument showed similar HL scores to those of our study. Chinese adolescents (49) , mean age of 13.4 years, had a mean HL score of 26.3, a little higher than the score obtained in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Students in the first and fifth grades accounted for 18.13, 23.35, 22.94, 19.35 and 16.23% of the sample, respectively. Reviewing the literature and referring to previous survey results, the current incidence of depressive symptoms among medical students in China is approximately 32% [ 2 ]. We set the tolerances at δ = 0.032, π = 0.32, α = 0.05, and u α/2 = 1.96.…”
Section: Methodsmentioning
confidence: 99%
“…Subclinical depression has a high incidence in the general population, ranging from 1.4 to 17.2% in the community. Among medical students in China, the incidence of subclinical depression is as high as 32% [ 2 ]. Social dysfunction is present not only in patients with clinical depression (MDD) but also in patients with subclinical depressive symptoms [ 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Esta puntuación representa alrededor del 68% de la máxima posible (37 puntos) según esa escala. Otros estudios(49)(50)(51) , utilizando el mismo instrumento HLAT-8, mostraron valores similares a los de esta investigación. Los adolescentes chinos(49) , con una media de edad de 13,4 años, evidenciaron una media de 26,3 puntos, resultado ligeramente superior al de este estudio.…”
unclassified
“…Los adolescentes chinos(49) , con una media de edad de 13,4 años, evidenciaron una media de 26,3 puntos, resultado ligeramente superior al de este estudio. Entre los universitarios de China, durante el período de la pandemia de COVID-19, la AeS resultó en 25,6 puntos(50) y entre los universitarios italianos fue de 27,4 puntos(51) .www.eerp.usp.br/rlae…”
unclassified